(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This study aims to measure the relationship between aggregate demand and the current account in Iraq during the period (2000 - 2022) using time series data at current prices, using the autoregressive distributed lag (ARDL) model, and using the extended Dickey-Fuller model to test the stability of the unit root, where all variables were The study is stable at the first difference, and the results of testing the long- and short-term equilibrium relationship (co-integration) between the variables showed the presence of a positive and significant effect on the aggregate demand on the current account in the short and long-term as a result of the high relative importance formed by oil exports in the formation of output in the economy. Iraq is rentier, as oil exports constituted (98.54%) of the total export structure. If this mostly rentier trend continues in the economy, the current account situation is unlikely to be affected in light of the rising prices and quantities of crude oil exported abroad. The research reached a set of results, the most important of which is the fragility of the Iraqi economy in the face of global economic crises as a result of the commodity concentration of exports through oil products, occupying a percentage of (98.54%) of the total export structure during the research period. The research also included a number of recommendations, the most important of which is diversifying sources of income. The heavy reliance on crude oil exports makes the Iraqi economy vulnerable to fluctuations in oil prices, and therefore, any decline in oil prices will lead to an imbalance in the structure of the current account, in addition to its impact on the entire economy.